2002
DOI: 10.1093/jpepsy/27.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Daily Hassles and Social Support as Predictors of Adjustment in Children With Pediatric Rheumatic Disease

Abstract: Interventions should focus on management of daily hassles and increasing social support for children with PRDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
2
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 25 publications
7
51
2
3
Order By: Relevance
“…Thus, our results are inconsistent with studies that found limited peer relations to correlate with depressive symptoms in children with SJRA. 39,40 In our study, most patients had active disease, but their parents reported no externalizing symptoms that differed from the healthy control subjects. This contradicts the report of behavior problems in male children with active disease 41 and confirms studies that found no significant deficits regarding these psychosocial functions.…”
Section: Discussionmentioning
confidence: 52%
“…Thus, our results are inconsistent with studies that found limited peer relations to correlate with depressive symptoms in children with SJRA. 39,40 In our study, most patients had active disease, but their parents reported no externalizing symptoms that differed from the healthy control subjects. This contradicts the report of behavior problems in male children with active disease 41 and confirms studies that found no significant deficits regarding these psychosocial functions.…”
Section: Discussionmentioning
confidence: 52%
“…These disorders are not curable, and the main goal of treatment is disease management, which includes reducing pain, controlling inflammation, maintaining function, and preventing deformities or persistent organ failure. [62] Rheumatologic disorders in pediatric patients are typically more severe clinically than the same disorders in adults, and may have significant psychiatric and medical consequences. These conditions are treated with potent immunosuppressive medications, steroids, and immune modulators that also may be associated with psychiatric side effects.…”
Section: Rheumatic Disordersmentioning
confidence: 99%
“…Children with rheumatologic disorders are at an increased risk for adjustment problems, particularly internalizing problems such as anxiety and depression, often seen in association with higher levels of family stress. Higher social support reduces the risk for these adjustment disorders [62]. Classmate and parental support appear to be the best predictor of adjustment [62], and in contrast, poor body image and lack of satisfaction with social support are most predictive of poor psychosocial adjustment and function [63].…”
Section: Rheumatic Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Los índices de fi abilidad y validez de la prueba original son buenos, así como los de la adaptación al español a partir de los trabajos de Bermúdez (1978a;1978b) y su versión comercial realizada por la sección de estudios de TEA Ediciones (Spielberger et al, 1982). El STAI y el STAI/E han sido también empleados en personas con enfermedades reumáticas (véa-se, p.ej., Reid, Lang y McGrath, 1997;von Weiss et al, 2002).…”
Section: Instrumentosunclassified